Daya Saing Perdagangan Daerah di Kabupaten Jember (Perspektif Kebijakan Publik) - Herman Cahyo Diartho (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
This research aims to know the policies that help in increasing the competitiveness of the subsector crops plantations in Kabupaten Jember. Analysis tools are used to find out the strategy of increasing competitiveness in the study was Analytical Hierarky Process (AHP). RCA analysis tools produce that plantation crops with tobacco commodities have the strongest competitiveness value of 5.45. The results of this research show that cooperation between regional policy as a policy that has the highest weight of 0.82.